Development of Stopmotion Video Animation Media in Qawa'Id Learning for Class XI Madrasah 'Aliyah Students | Pengembangan Media Animasi Stopmotion Video dalam Pembelajaran Qawa’Id pada Siswa Kelas XI Madrasah ‘Aliyah - Djian Ariska; Ninik Indrawati; Ammar Zainuddin (Mantiqu Tayr: Journal of Arabic Language, 2022)
This research is motivated by various problems and obstacles in the qawā'id learning this is also because teachers do not innovate in using learning media in delivering qawā'id. With this, the researcher developed audiovisual media in the form of stopmotion video animation for learning Arabic qawā'id, with the stopmotion video animation media containing moving writing along with explanations and examples of qawā'id material which was able to make students get a real picture of the application of Arabic rules.The type of research used Research and Development (R&D) using a modified Borg and Gall development model. From the results of the analysis, the average assessment of media experts and stopmotion animation learning media materials is 70.5% and is declared "valid" and suitable for use as qawā'id learning media.